2013
DOI: 10.1002/jgra.50357
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term loss and re‐formation of the outer radiation belt

Abstract: [1] The Earth's outer radiation belt is known to vary often and significantly on various time scales. In this study, we have used the data of various instruments onboard the THEMIS spacecraft to study long-term changes of the outer radiation belt electrons around the year 2009. We find that the entire outer belt became extremely weak for nearly a year and was practically lost a few times, each time lasting~20 days up to~2 months, before eventually re-forming. This was revealed at a wide energy range from sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 83 publications
1
16
0
2
Order By: Relevance
“…Even though EMIC waves generally do not cause very strong pitch angle scattering for low pitch angle electrons with energies between 226 keV and 1 MeV, hiss waves can interact with these electrons and result in precipitation loss to the atmosphere (Li et al, ; Ni et al, ; Thorne, ). However, hiss waves are not responsible for rapid dropouts in general, since timescales of pitch angle scattering to the loss cone due to hiss are approximately 10 h to several days (Lee et al, ; Ma et al, ; Summers et al, ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Even though EMIC waves generally do not cause very strong pitch angle scattering for low pitch angle electrons with energies between 226 keV and 1 MeV, hiss waves can interact with these electrons and result in precipitation loss to the atmosphere (Li et al, ; Ni et al, ; Thorne, ). However, hiss waves are not responsible for rapid dropouts in general, since timescales of pitch angle scattering to the loss cone due to hiss are approximately 10 h to several days (Lee et al, ; Ma et al, ; Summers et al, ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For this study we use the chorus wave data observed on the THEMIS satellites over a prolonged period [ Angelopoulos , ]. Specifically, we first construct the prediction model of chorus amplitudes using the data for about a 5 year period, from July 2007 to July 2012—excluding about 4 months from 1 June 2009 when the solar wind conditions and the magnetospheric activities were unusually weak [ Lee et al ., ] and the determination of the plasmapause location could not be made appropriately (see below). Then, the developed prediction model is tested for a separate 1.5 years period from August 2012 to January 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The bulk of current radiation belt research is largely based on the interaction of electrons with plasma waves of a wide frequency range within the inner magnetosphere [e.g., Bortnik and Thorne, 2007;Shprits et al, 2008Shprits et al, , 2013Kim et al, 2012;Lee et al, 2013;Ni et al, 2013;Glauert et al, 2014]. Various types of waves have been observed in different regions and wide frequency domains and are believed to play a role in various aspects and to different degrees.…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's radiation belt electron dynamics is highly complex, resulting from a delicate, competitive balance between their transport, energization, and loss processes, and also shows strong dependence on a number of factors including solar wind driving condition, geomagnetic activity, electron kinetic energy, spatial location, and time [e.g., Li et al, 1997;Reeves et al, 1998Reeves et al, , 2003Meredith et al, 2003;Lee et al, 2013;Ni et al, 2013;Thorne et al, 2013aThorne et al, , 2013bBaker et al, 2013aBaker et al, , 2014aBaker et al, , 2014b. It has been known that geomagnetic storms can either increase or decrease the fluxes of radiation belt relativistic electrons, with about half of all storms increasing the relativistic electron fluxes, one quarter decreasing the fluxes, and the remaining quarter producing little or no change in the fluxes [Reeves et al, 2003].…”
Section: Introductionmentioning
confidence: 99%